MSC-derived immunomodulatory extracellular matrix functionalized electrospun fibers for mitigating foreign-body reaction and tendon adhesion. (1st October 2021) - Dong, Lili; Li, Linhao; Song, Yang; Fang, Yunnan; Liu, Jinlin; Chen, Peixing; Wang, Sixiang; Wang, Chunli; Xia, Tingting; Liu, Wanqian; Yang, Li
Abstract: Adhesion formation during tendon healing remains a severe problem in clinical practice. Multiple factors contribute to postoperative adhesion formation, and macrophage-driven inflammation is thought to be greatly involved in this process. We hypothesize that reducing macrophage-mediated inflammation in the injured tendon by regulating M1 to M2 macrophage polarization may effectively inhibit adhesion formation. Here, we developed an acellular immunomodulatory biomaterial consisting of an electrospun polycaprolactone/silk fibroin (PCL/SF) composite fibrous scaffold functionalized with mesenchymal stem cell (MSC)-derived extracellular matrix (ECM). To enhance the immunoregulatory potential of MSCs, we performed inflammatory licensing with IFN-γ to obtain immunomodulatory ECM (iECM). Proteomic analyses of MSCs and their secreted ECM components from different culture conditions revealed the MSC-ECM molecular signatures and the potential mechanism of ECM immunoregulation. Then, the immunoregulatory potential of the iECM-modified scaffold was evaluated in vitro and in vivo . Relative to the PCL/SF fibrous scaffold, the iECM-functionalized scaffold facilitated M2 macrophage polarization and inhibited the expression of multiple cytokines (IL-1β, IL-6, CXCL11, IL-10, IL-1R2, and TGF-β1) in vitro, strongly suggesting the immunosuppressive ability of iECM derived from inflammatory licensed MSCs. Consistent with the in vitro findings, the results of rat subcutaneous implantation indicated that a markedly lower foreign-body reaction (FBR) was obtained in the PCL/SF-iECM group than in the other groups, as evidenced by thinner fibrotic capsule formation, less type I collagen production and more M2-type macrophage polarization. In the rat Achilles tendon injury model, the PCL/SF-iECM scaffold greatly mitigated tendon adhesion with clear sheath space formation between the tendon and the scaffold. These data highlight the immunomodulatory potential of iECM-functionalized fibrous scaffolds to attenuate FBR by modulating M2 macrophage polarization, thereby preventing tendon adhesion. Statement of significance: Electrospun PCL/SF fibrous scaffolds functionalized with ECM secreted by MSCs stimulated by inflammatory factor IFN-γ was developed that combined physical barrier and immunomodulatory functions to prevent tendon adhesion formation. PCL/SF micro-nanoscale bimodal fibrous scaffolds prepared by emulsion electrospinning possess high porosity and a large pore size beneficial for nutrient transport to promote intrinsic healing; moreover, surface modification with immunomodulatory ECM (iECM) mitigates the FBR of fibrous scaffolds to prevent tendon adhesion. The iECM-functionalized electrospun scaffolds exhibit powerful immunomodulatory potency in vitro and in vivo . Moreover, the iECM-modified scaffolds, as an anti-adhesion physical barrier with immunomodulatory ability, have an excellent performance in a rat Achilles tendon adhesion model. MSC secretome-based therapeutics, as an acellular regenerative medicine strategy, are expected to be applied to other inflammatory diseases due to its strong immunoregulatory potential. Graphical abstract: Image, graphical abstract